Molecular imaging research in atherosclerosis: A 23-year scientometric and visual analysis - Pan, Juhong; Chen, Yueying; Hu, Yugang; Wang, Hao; Chen, Wenwei; Zhou, Qing (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Cardiovascular and cerebrovascular diseases are a major global health problem, and the main cause is atherosclerosis. Recently, molecular imaging has been widely employed in the diagnosis and therapeutic applications of a variety of diseases, including atherosclerosis. Substantive facts have announced that molecular imaging has broad prospects in the early diagnosis and targeted treatment of atherosclerosis. Objective: We conducted a scientometric analysis of the scientific publications over the past 23 years on molecular imaging research in atherosclerosis, so as to identify the key progress, hotspots and emerging trends. Methods: Original research and reviews regarding molecular imaging in atherosclerosis were retrieved from the Web of Science Core Collection database. Microsoft Excel 2021 were used to analyze the main findings. CiteSpace, VOSviewer and a scientometric online platform was applied to perform visualization analysis of co-citation of journals and references, co-occurrence of keywords, as well as collaboration between countries/regions, institutions, authors. Results: A total of 992 publications were finally included, which published by 650 authors in 487 institutions from 48 countries/regions. The USA and Harvard University were the top country and institution in terms of the number and centrality of publications in this domain, with 506 and 91 papers and a centrality of 0.48 and 0.18, respectively. Jaffer FA was the most productive authors (42 papers), while LIBBY P had the most co-citations (245). CIRCULATION was the top co-cited journal with a frequency of 758, followed by ARTERIOSCL THROM VAS (599). The co-citation references analysis identified 16 clusters with a well-structured network (Q=0.7491) and highly convincing clustering (S=0.8992). All the studies calculated by keyword co-occurrence, were divided into five clusters: “positron emission tomography”, “magnetic resonance imaging”, “ultrasonography”, “inflammation” and “nanoparticle”. Hot topics mainly focused on Alzheimer's disease, contrast agent, vulnerable plaque, microbubble, and drug delivery. Sodium fluoride ⁃PET, photoacoustic imaging and vascular calcification were identified as the potential trends. Conclusions: Molecular imaging research in atherosclerosis has attracted extensive attention in the academia, while the challenges of clinical transformation faced in this field had been described. The finds of the present research can inform funding agencies and researchers of future directions.